Ultrasound Guidance for Vaginal Drainage of Postoperative Pelvic Hematoma: A Case Report - Thomas E. Snyder; Sebastian Faro (Hindawi Limited, 1994)
Background: Postoperative pelvic fluid collection is almost a universal consequence of gynecologic surgery. At one end of the spectrum are minimal collections of peritoneal fluid or blood that are clinically inconsequential. At the other end are hematomas and abscesses requiring active intervention for the patient to recover.